Pengaruh Media Powtoon Terhadap Hasil Belajar Peserta Didik Pada Pembelajaran IPA Di Sekolah Dasar - Heny Endang Wahyuni; Zulkarnain; Roikhatul Janah (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2025)
This study aims to determine the effect of using Powtoon-based video learning media on the cognitive learning outcomes of students in grade IV at SDN 39 Pontianak. The research design used a quasiexperimental approach with a non-equivalent control group design. The sample in this study consisted of 53 students, comprising class IVA as the experimental class and class IVB as the control class. The independent variable in this study was the use of Powtoon-based video learning media, and the dependent variable was science learning outcomes. The results showed that the learning outcomes of students after using Powtoon-based video learning media in the experimental class increased, with a pretest average score of 48.80 and a posttest average score of 78.04. 4) Based on the results of the independent sample ttest for the experimental class, a significant value of 0.039 < 0.05 was obtained. Thus, H0 was rejected and Ha was accepted, meaning that there was an effect on the use of Powtoon-based video learning media on student learning outcomes in the subject of Earth's gravitational force in grade IV at SDN 39 Pontianak.